Pedagogik Transformatif Berbasis Industri: Pendekatan Transdisipliner Dalam Implementasi Merdeka Belajar - Jahudin, Andi Aswad; Amelia, Aas; Madhakomala, R (Universitas Pakuan, 2025)
INDUSTRY-BASED TRANSFORMATIVE PEDAGOGY: A TRANSDISCIPLINARY APPROACH TO THE IMPLEMENTATION OF MERDEKA BELAJARThe era of technological disruption and industrial transformation demands that Indonesia's vocational education system shift from conventional learning models toward more contextual, collaborative, and transdisciplinary approaches. This study develops a conceptual framework called PETALS (Pedagogic Empowerment Through Industry-Linked Transdisciplinary System) in response to the low level of integration between industry needs and teaching practices in vocational high schools (SMK). By integrating elements of transformative pedagogy, experiential learning, design thinking, and Triple Helix collaboration, PETALS is structured around six core pillars: (1) industry-based professional development for teachers; (2) embedded curriculum co-designed with industry partners; (3) transdisciplinary project-based learning; (4) portfolio-based authentic assessment; (5) long-term industry partnerships; and (6) sustainable policy support. The methodology employed includes a systematic literature review of 70 sources from Scopus, Google Scholar, Garuda, and national policy documents (2015–2024), along with a simulated application of the framework at SMK Negeri 1 Cikarang. Findings from the simulation and literature synthesis indicate that PETALS enhances curriculum relevance to industry demands, strengthens students’ reflective and collaborative competencies, and provides an integrated model of authentic assessment. Modular implementation of PETALS is recommended as a pilot across various vocational sectors and as a reference for national vocational policy development aligned with the Vision of Indonesia Emas 2045.